Self-Esteem Mediates the Relationships Between Social Support, Subjective Well-Being, and Perceived Discrimination in Chinese People With Physical Disability - Ji, Yinyin; Rana, Chandni; Shi, Congying; Zhong, Yuan (Frontiers in Psychology, 2019)
Background: Disabilities have a negative effect on mental health and individuals with such conditions are especially susceptible to mental disorders. Previous research has established that in normal population, social support is significantly correlated with subjective well-being (SWB) through mediating variables; however the internal mechanism underlying this in people with physical disability remains unclear. This study aims to examine whether self-esteem and perceived discrimination play a mediating role in the relationship between social support and SWB in a sample of people with physical disability in China. Methods: A total of 210 people with physical disability of Chinese ethnicity were recruited to complete a series of questionnaires. This included the Chinese Social Support Rating Scale (CSSRS), Rosenberg Self-esteem Scale (RSES), Disability Discrimination Perception Questionnaire (DDPQ) and the Chinese Happiness Inventory (CHI). Path analysis was implemented on the data. Results: The model showed excellent fit to data: χ2 = 2.314, P > 0.05; Root-mean-square error of approximation (RMSEA) = 0.079; Standardized root-mean residual (SRMR) = 0.035; Comparative fit index (CFI) = 0.989, and Tucker–Lewis index (TLI) = 0.936. The results showed that self-esteem significantly mediated the relationship between social support and SWB, and perceived discrimination in people with physical disability. However, there is no mediating effect of perceived discrimination between social support and SWB. Conclusion: These findings demonstrate that self-esteem may be a critical resource in mediating the relationships between social support, SWB and perceived discrimination in people with physical disability.